Subgingival air‐polishing with erythritol during periodontal maintenance: Randomized clinical trial of twelve months - Müller, Nada; Moëne, Raphaël; Cancela, José A.; Mombelli, Andrea (Journal of clinical periodontology, 2014)
To evaluate repeated subgingival air-polishing in residual pockets with a new erythritol powder containing 0.3% chlorhexidine. Single-centre, examiner masked, randomized clinical trial of 12 months with a two-arm, within-subject parallel design. Fifty patients in periodontal maintenance were monitored in 3-month intervals. At months 0, 3, 6 and 9, all sites presenting with a probing depth (PD) >4 mm were subject to subgingival air-polishing (test side) or ultrasonic debridement (control side). The primary endpoint was presence/absence of PD >4 mm after 12 months. Totally 6918 sites were monitored at baseline, 457 of them had a PD >4 mm (range 5-9 mm). The number of pockets >4 mm per subject, PD and bleeding on probing were significantly lower at month 12. Differences between test and control were not significant. There was a significant difference in favour of air-polishing for the perception of pain/discomfort. Differences of frequencies at >1000 and >100,000 cells/ml of six microorganisms between baseline and month 12 were not significant. At month 12, test sites were less frequently positive for Aggregatibacter actinomycetemcomitans at >1000 cells/ml than controls, and counts never exceeded 100,000 cells/ml. Repeated subgingival air-polishing reduced the number of pockets >4 mm similar to ultrasonic debridement. It was safe and induced less pain.